Barriers of moral development among adolescents: a content analysis of empirical literature - Abd Rashid, Adnan; Mamat , Arifin (2013)
Present-day Muslims are generally aware of moral decline of adolescents. While socio-moral diseases are becoming the common, many Muslims even know their causes, at least the superficial ones if not their root causes. Parents are deeply concerned about this problems and very much eager to see it resolved soon, especially by its political, religious, and intellectual leaders. In fact in microscopic view parents are the main power of a nation or society. So their involvement in saving the adolescents from degradation is very important and any solution regarding adolescents’ moral degeneration and decline must be sought and applied through active participation of the parents. Therefore the present study aims to enlighten the parents by examining the barriers of moral development among adolescents. So, the researcher has studied rigorously all available journal articles which are managed by popular online databases and subscribed by IIUM library. He has searched the databases with appropriate terms and their family words. During searching journal papers he has only accepted those causes of moral decline which had been empirically tested before. The findings have implication for raising parental awareness on protecting the adolescents from the agents of moral decline since their early childhood. It is hoped that this will pave the way of constructing a happy and safe society.